DOMESTIC TOURISM FLOWS OF IVANO-FRANKIVSK REGION ANALYSIS BASED ON MOBILE COMMUNICATION DATA IN 2018. PART 1 - Perederko , V.P. (The actual problems of regional economy development, 2019)
Official statistics cannot reflect the true picture of domestic tourism flows entering the Precarpathian region because of the imperfection of the methodology for calculating. The purpose of the article is to provide an approximate domestic tourism flows estimation based on data analysis that illustrate the movement of subscribers of the mobile communication in terms of the administrative districts of Ivano-Frankivsk region. Mobility monitoring is limited; first, by the fact that it does not contain information about the purpose of subscribers’ short-term stay in a certain territory; therefore, we cannot all of them count as excursionists or tourists without exception. However, the application of the innovative approach of domestic tourism flows analyzes and quantitative measuring of region’s attendance based on monitoring of interregional mobility of communication operator subscribers is a promising direction for further researches. The article is devoted to the short-term interregional movements (migrations) of the population of Ukraine analyzes in the context of studying the domestic tourism flows of Prykarpattya in terms of administrative districts (local destinations) of Ivano-Frankivsk region based on monitoring of interregional mobility of the communication operator subscribers in 2018. The popular local destinations of the region and the geography of their visitors, which can be considered as target audiences of actual and potential tourists, are determined. Investigated seasonality of movements (migrations) and duration of stay in local destinations – the mobile subscribers flows leaders – allowed to identify mobility patterns, traffic transit signs, etc. The mobile network data use in means of statistical information in the field of tourism is of a great importance for the region's economy, since tourism is one of the regional development priorities.